Algorithmic implementation to achieve high speed mathematical addition on Silicon for 128 bits and larger - Weng, Fook Lee (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.